Study on health seeking behaviour and determinants of undiagnosed hypertension in poor households in the Philippines, part of the RESPOND study (SHARP-RESPOND). - Hau Man Harmony To; Benjamin Palafox; Dina Balabanova; Lia Palileo-Villanueva; Martin McKee (PLOS Global Public Health)
Hypertension is one of the leading preventable causes of premature death. Although it can be effectively managed with relatively simple interventions, up to 50% of individuals with hypertension in low- and middle-income countries (LMICs) remain undiagnosed. Key factors influencing the health-seeking behaviour of patients with hypertension include household wealth, knowledge about hypertension, perceptions of treatment effectiveness, and access to blood pressure measurement. However, evidence on the facilitators and barriers to hypertension diagnosis in low-income households within LMICs remains inconsistent. This study aims to describe the characteristics and health-seeking behaviours of individuals with undiagnosed hypertension in low-income households in the Philippines and identify the factors influencing undiagnosed hypertension. The study included 516 people with hypertension from low-income households in the Philippines as part of the RESPOND study. Characteristics of participants with undiagnosed hypertension were compared to those with diagnosed hypertension to identify determinants of undiagnosed cases. A follow-up survey one year later gathered data on whether undiagnosed participants had subsequently received a formal diagnosis. In this study, 26.6% of people with hypertension in low-income households were undiagnosed. Over one year, only 25.4% of these undiagnosed individuals received a formal diagnosis. Factors associated with lower odds of undiagnosed hypertension included belief in the effectiveness of Western medicine, recent blood pressure measurement, receipt of health information in the preceding year, presence of comorbidities, and participation in social organisations. Conversely, living in rural areas, employment, and belief in the effectiveness of traditional medicine were linked to higher odds of remaining undiagnosed. A substantial proportion of people with hypertension in low-income households in the Philippines remain undiagnosed. Addressing this issue requires a multifaceted approach targeting the social determinants of health and addressing specific barriers to hypertension diagnosis. Insights from this study can inform strategies to improve hypertension control in other LMICs.